Adaptability of a generic wave energy converter to different climate conditions. (June 2015) - de Andres, A.; Guanche, R.; Vidal, C.; Losada, I.J.
Abstract: This study evaluates the influence of wave climate tunability on the performance of a generic Wave Energy Converter (WEC) for different climate scenarios. The generic WEC is assumed to be composed of an array of heaving, floating cylinders. In this study, two natural periods for the cylinders of 4 s and 8 s (typical of enclosed seas and the mean Atlantic swell, respectively) and a location-tunable cylinder are considered to evaluate the influence of tuning on the power performance of the cylinder. The WEC power matrix is computed using a frequency domain model, and the performance of the WEC is evaluated along the global coasts; the met-ocean data originated from the global reanalysis database (GOW) from Reguero et al. (2012). The performance of the WEC is evaluated using two parameters: the capture width ratio (CWR), which evaluates the efficiency of the converter at each location, and the kW/Ton (KWT) parameter, which evaluates the efficiency of the converter using "economic" terms. Tuning a converter for each location displayed a positive CWR; however, the KWT was low after WEC tuning because of the weight of the structures required to tune the converter that experiences high peak periods. Highlights: Matching WEC performance with local wave conditions is positive regarding CWR. Matching WEC performance with local wave conditions is negative in terms of mass. Tuning a cylinder for high wave periods requires very heavy structures. "Small" structures are recommended with a constant design for all the locations.